York Minster - Purey-Cust, Arthur P. (Arthur Perceval), 1828-; Ansted, Alexander, 1859-1948 (Salt Lake City, UT : Project Gutenberg, 2011)
"York Minster" by Arthur P. Purey-Cust is a historical account published during the late 19th century. This book explores the architectural and historical significance of York Minster, a prominent cathedral in England. It provides a detailed narrative of the church's development, its artistic features, and the interplay between historical events and the church's evolution. In "York Minster," the author delves into the rich history of the cathedral, outlining its construction from its early beginnings to its status as one of the greatest Gothic buildings in Europe. Purey-Cust highlights key figures involved in its development, such as Archbishops and various benefactors, while recounting significant events that shaped its architecture, including restorations after fires and changes in architectural styles over the centuries. The text is richly illustrated and emphasizes the blend of religious significance and artistic value, making it a vital resource for understanding not only York Minster itself but also the broader context of ecclesiastical architecture in England. (This is an automatically generated summary.)
Release date is 2011-06-28
E-text prepared by Brownfox and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://www.archive.org)
Keywords: Cathedrals -- England; York Minster